2006
DOI: 10.1086/500584
|View full text |Cite
|
Sign up to set email alerts
|

Observational Properties of Protoplanetary Disk Gaps

Abstract: International audienceWe study the effects of an annular gap induced by an embedded protoplanet on disk scattered light images and the infrared spectral energy distribution (SED). We find that the outer edge of a gap is brighter in the scattered light images than a similar location in a gap-free disk. The stellar radiation that would have been scattered by material within the gap is instead scattered by the disk wall at the outer edge of the gap, producing a bright ring surrounding the dark gap in the images. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
36
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 26 publications
5
36
0
Order By: Relevance
“…For example, if the gap is cleared by the planet to a fraction of the surrounding density, the disk is not directly irradiated, but is shadowed by the inner wall of the gap (Varnière et al 2006). This mild heating causes a temperature drop at the inner gap wall, which results in a depressed CO flux.…”
Section: Discussionmentioning
confidence: 99%
“…For example, if the gap is cleared by the planet to a fraction of the surrounding density, the disk is not directly irradiated, but is shadowed by the inner wall of the gap (Varnière et al 2006). This mild heating causes a temperature drop at the inner gap wall, which results in a depressed CO flux.…”
Section: Discussionmentioning
confidence: 99%
“…Lin & Papaloizou 1979, 1986. A gap carved by a single planet has very little impact on the spectral energy distribution (SED), but could be identified by imaging of the disk (Steinacker & Henning 2003;Varnière et al 2006;Wolf et al 2007). Nonetheless, a class of so-called transitional disks have been identified on the basis of their low near-infrared excess, which is apparently caused by depleted inner regions (Strom et al 1989;Muzerolle et al 2004;Calvet et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Vorobyov et al (2013) and Zakhozhay et al (2013) show that a presence of hot and massive (32 -64 M J ) fragments -proto-brown dwarfs during the first few 10,000 years -initiate an additional peak in SEDs at 5 -10 µm. Varnière et al (2006), considered the example of a 2 Jupiter mass planet on a very close orbit to the star, and found that SEDs from discs with gaps may not only have a reduced emission at λ ∼ 5 − 20 µm due to the removal of the emission from the gap, but also may have a measurable excess emission at longer wavelengths (∼ 10 − 100 µm), that rises from the heat-2 O.V. Zakhozhay ing of the vertical disc wall at the outer edge of the gap.…”
Section: Introductionmentioning
confidence: 99%